Allelic Switching of DLX5, GRB10, and SVOPL during Colorectal Cancer Tumorigenesis - Arnoud Boot; Jan Oosting; Saskia Doorn; Sarah Ouahoud; Marina Ventayol Garcia; Dina Ruano; Hans Morreau; Tom van Wezel (International Journal of Genomics)
Allele-specific expression (ASE) is found in approximately 20-30% of human genes. During tumorigenesis, ASE changes due to somatic alterations that change the regulatory landscape. In colorectal cancer (CRC), many chromosomes show frequent gains or losses while homozygosity of chromosome 7 is rare. We hypothesized that genes essential to survival show allele-specific expression (ASE) on both alleles of chromosome 7. Using a panel of 21 recently established low-passage CRC cell lines, we performed ASE analysis by hybridizing DNA and cDNA to Infinium HumanExome-12 v1 BeadChips containing cSNPs in 392 chromosome 7 genes. The results of this initial analysis were extended and validated in a set of 89 paired normal mucosa and CRC samples. We found that 14% of genes showed ASE in one or more cell lines and identified allelic switching of the potential cell survival genes DLX5, GRB10, and SVOPL on chromosome 7, whereby the most abundantly expressed allele in the normal tissue is the lowest expressed allele in the tumor and vice versa. We established that this allelic switch does not result from loss of imprinting. The allelic switching of SVOPL may be a result of transcriptional downregulation, while the exact mechanisms resulting in the allelic switching of DLX5 and GRB10 remain to be elucidated. In conclusion, our results show that profound changes take place in allelic transcriptional regulation during the tumorigenesis of CRC.